PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUASAN PELANGGAN JNE CABANG BATAM - Sepiyani, Sepiyani; Saputra, Asron (SCIENTIA JOURNAL, 2019)
This research as purpose for knowing effect of service quality on the satisfaction of JNE Branch customer Batam, and effect prices on the satisfaction of JNE Branch customer in Batam, and affect of service quality ang prices on the satisfaction of JNE Customer in Batam Branch. The method this research a quantitative approach with associative design. The population of this research is all JNE customers in Batam Branch, sample 299 people. Method used questionnaire with accidental sampling technique. The data analysis technique used in this study is validity and reliability testing, multiple linear regression analysis and coefficient of determination with the help of SPSS 21. Besad on the results of research, it can be concluded that service quality has positive effect on the satisfaction of JNE Branch Batam Customers. Price has positive affect on the satisfaction of JNE Branch Batam customers, and service quality and price together have positive and significan effect on the satisfaction of JNE Branch Batam Customers. Overall service quality and price veariables affect customer satisfaction by 0,510, meaning that 51% of Batam Branch JNE Customers satisfaction influenced by service quality and price variables, while remaining 49% is influenced by other variables not discussed in this study.